2008
DOI: 10.1590/s0100-204x2008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme activities and pectin breakdown of sapodilla submitted to 1-methylcyclopropene

Abstract: -The objective of this work was to investigate the influence of 1-methylcyclopropene (1-MCP) at 300 nL L -1 on activities of cell wall hidrolytic enzymes and pectin breakdown changes which Sapodilla (Manilkara zapota cv. Itapirema 31) cell wall undergoes during ripening. Sapodilla were treated with ethylene antagonist 1-MCP at 300 nL L -1 for 12 hours and then, stored under a modified atmosphere at 25ºC for 23 days. Firmness, total and soluble pectin and cell wall enzymes were monitored during storage. 1-MCP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…25 % until day 16 and then a slight decrease was observed. Previous works reported similar behaviour for PME activity, mostly in tropical fruits like sapodilla, guava, papaya and carambola (Morais et al 2008;Miranda et al 2002;Abu-Goukh and Bashir 2003;Ali et al 2004).…”
Section: Enzymatic Activitymentioning
confidence: 53%
See 1 more Smart Citation
“…25 % until day 16 and then a slight decrease was observed. Previous works reported similar behaviour for PME activity, mostly in tropical fruits like sapodilla, guava, papaya and carambola (Morais et al 2008;Miranda et al 2002;Abu-Goukh and Bashir 2003;Ali et al 2004).…”
Section: Enzymatic Activitymentioning
confidence: 53%
“…It is known that pectin methylesterase (PME: EC 3.1.1.11) is correlated with texture changes of fruits and vegetables. The generally high metabolic activity during ripening, results in higher PME activity and, consequently, greater solubilisation of pectin (Morais et al 2008). A significant (p < 0.05) decrease of PME activity, ca.…”
Section: Enzymatic Activitymentioning
confidence: 99%
“…Similarly, Morais et al (2008) found that sapodilla fruit treated with 300 nL/L of 1-MCP, presented a slower rate of softening in comparison with untreated fruit.…”
Section: Firmnessmentioning
confidence: 78%
“…The evidence suggests that 1-MCP was able to prolong shelf life by delaying ripening. Similarly, Jeong et al (2002) found that the maximum PME activity was delayed in avocados treated with 1-MCP, in comparison with the control, while, Morais et al (2008) observed that the treatment with 300 nL/L of 1-MCP in sapodilla resulted in a significant delay of maximum PME activity, when compared the untreated fruit. Furthermore, after 18 and 25 days in refrigeration, the fruits treated with 1-MCP showed similar values for maximum PME activity on reaching ripeness for consumption (Figure 3).…”
Section: Enzymatic Activity Of Pectin Methyl Esterase (Pme)mentioning
confidence: 84%
“…Na presença do potássio, ocorre a redução da pectina total e, consequentemente, o aumento da pectina solúvel. Morais et al (2008) verificaram, durante o amadurecimento de sapoti, concentrações de pectina total e solúvel superiores aos deste trabalho, assim como redução da concentração de pectina total, à medida que a pectina solúvel aumentava.…”
Section: Resultsunclassified